Dynapenic abdominal obesity and susceptibility to fall: a prospective analysis of the Osteoarthritis Initiative - Veronese, Nicola; Koyanagi, Ai; Soysal, Pinar; Bolzetta, Francesco; Dominguez, Ligia J.; Barbagallo, Mario; Sabico, Shaun; Al-Daghri, Nasser M.; Smith, Lee (Frontiers in Nutrition, 2023)
Background: The prediction of the risk of falling remains a challenge in geriatric medicine and the identification of new potential reversible risk factors is a public health priority. In this study, we aim to investigate the association between DAO (dynapenic abdominal obesity) and incident falls in a large sample of older people with knee OA (osteoarthritis) or at high risk for this condition, over eight years of follow-up. Methods: DAO was defined using a waist circumference more than 102 cm in men and 88 cm in women and a concomitant presence of dynapenia, defined as a time over 15 second in the five times chair stands time. Falls, during follow-up, were recorded using self-reported information in the previous year. A logistic binary regression analysis was run, adjusted for potential confounders at the baseline, reporting the data as odds ratios (ORs) with their 95% confidence intervals (CIs). Results: Overall, 3,844 subjects were included, majority of whom had abdominal obesity. Across the 8 years of follow-up, 2,695 participants fell vs. 1,149 not reporting any fall. Taking those without DAO as reference, the presence of only dynapenia was not associated with risk of falls (OR=1.18;95%CI: 0.73-1.91; p=0.50), whilst the presence of abdominal obesity (OR=1.30; 95%CI: 1.09-1.56; p=0.004) and DAO (OR=1.31; 95%CI:1.01-1.73; p=0.04) were significantly associated with a higher risk of incident falls. Conclusions: DAO significantly increased risk of falls as well as the presence of abdominal obesity.